Determinants of caregiver's knowledge and practices regarding childhood fever management in a developing setting: a multi-centre cross-sectional assessment - Ibrahim A. Ogunyinka; Kazeem A. Oshikoya; Kazeem B. Yusuff; Yusuf Tahir; Mohammed Yahaya; Sulaiman B. Adeniye; Innocent E. Oforkansi (Frontiers Media S.A., 2023)
IntroductionFever is both a sign of various diseases (chief of which are infectious in nature) and an adverse effect of certain interventions (e.g. vaccines, drugs) in the pediatric population. It elicits anxiety among caregivers and healthcare professionals alike resulting in non-evidence based practices, adverse medication administration events, waste of scarce resources and overutilization of health facilities. The determinants of these practices among caregivers in the domiciliary contexts have not been well characterized in developing settings.MethodsWe assessed the knowledge and practices of childhood fever and their determinants among caregivers in domiciliary settings in Northern Nigeria using a 41-item questionnaire between August 2020 and February 2021.ResultsThe questionnaire is reliable (knowledge: Cronbach's Alpha = 0.689; practice: Cronbach's Alpha = 0.814) and collected data on a total of 2,400 caregiver-child pairs, who participated in the study. Over two-third (68.3%; 1,640) of the caregivers expressed fever phobic tendencies. Paracetamol was the most commonly used medication and constituted 31.3% of medication administration adverse events reported by the caregivers. Only one out of every six knowledgeable caregivers engaged in evidence-based home childhood fever management practices (7% vs. 41.6%) with being a primary caregiver [Knowledge: odd ratio (OR): 2.81, 95% CI: 0.38; 5.68; p value: 0.04; Practice: OR: 1.65, 95% CI: 0.09; 7.33; 0.02] and having a child/children aged ≤3 years (knowledge: OR: 7.03, 95% CI: 4.89; 9.67, p value: 0.003; practice OR: 3.11, 95% CI: 1.27; 8.59, 0.007) determining both the knowledge and practices of childhood fever management in a household.ConclusionsThe knowledge and practice of childhood fever management among caregivers were sub-optimal with being a primary caregiver and having a child/children aged ≤3 years being the significant determinants of each domain. These gaps underscore the dire need for targeted strategies aimed at improving childhood fever management by educating caregivers.